K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 9 2020

A = 4acx + 4bcx + 4ax + 4bx ( đã sửa '-' )

= 4x( ac + bc + a + b )

= 4x[ c( a + b ) + ( a + b ) ]

= 4x( a + b )( c + 1 )

B = ax - bx + cx - 3a + 3b - 3c

= x( a - b + c ) - 3( a - b + c )

= ( a - b + c )( x - 3 )

C = 2ax - bx + 3cx - 2a + b - 3c

= x( 2a - b + 3c ) - ( 2a - b + 3c )

= ( 2a - b + 3c )( x - 1 )

D = ax - bx - 2cx - 2a + 2b + 4c

= x( a - b - 2c ) - 2( a - b - 2c )

= ( a - b - 2c )( x - 2 )

E = 3ax2 + 3bx2 + ax + bx + 5a + 5b

= 3x2( a + b ) + x( a + b ) + 5( a + b )

= ( a + b )( 3x2 + x + 5 )

F = ax2 - bx2 - 2ax + 2bx - 3a + 3b

= x2( a - b ) - 2x( a - b ) - 3( a - b )

= ( a - b )( x2 - 2x - 3 )

= ( a - b )( x2 + x - 3x - 3 )

= ( a - b )[ x( x + 1 ) - 3( x + 1 ) ]

= ( a - b )( x + 1 )( x - 3 )

13 tháng 12 2018

\(\left(x^2-5x+8\right)^2-6x+8\)

\(=x^4+25x^2+64-10x^3-80x+16x^2-6x+8\)

\(=x^4-10x^3+41x^2-86x+72\)

\(=x^3\left(x-2\right)-8x^2\left(x-2\right)+25x\left(x-2\right)-36\left(x-2\right)\)

\(=\left(x-2\right)\left(x^3-8x^2+25x-36\right)\)

\(=\left(x-2\right)\left[x^2\left(x-4\right)-4x\left(x-4\right)+9\left(x-4\right)\right]\)

\(=\left(x-2\right)\left(x-4\right)\left(x^2-4x+9\right)\)

24 tháng 9 2017

ta có: \(\left(a+b+c\right)^2+\left(a+b-c\right)^2-4c^2=\left(a+b+c\right)^2+\left(a+b-c-2c\right)\left(a+b-c+2c\right).\)

                                                                                         \(=\left(a+b+c\right)^2+\left(a+b-3c\right)\left(a+b+c\right)\)

                                                                                          \(=\left(a+b+c\right)\left(a+b+c+a+b-3c\right)\)

                                                                                           \(=2\left(a+b+c\right)\left(a+b-c\right)\)

24 tháng 9 2017

(a+b+c)^2+(a+b-c)^2-4c^2

=(a^2+b^2+c^2+2ab+2bc+2ac)+(a^2-2ab+b^2-2ac+c^2-abc)-4c^2

=a^2+b^2+c^2+2ab+2bc+2ac+a^2-2ab+b^2-2ac+c^2-abc-4c^2

=(a^2+a^2)+(b^2+b^2)+(c^2+c^2)+(2ab-2ab)+(2bc-2bc)+(2ac-2ac)-4c^2

=2a^2+2b^2+2c^2-4c^2

=(2a^2+2b^2)+(2c^2-4c^2)

=2*(a^2+b^2)+2c^2*(1-2)

13 tháng 10 2016

a) = (xyz+xy) +(z+1) +(yz+zx)+(x+y)

 = xy(z+1) +(z+1)+z(x+y)+(x+y)

= (z+1)(xy+1)+(x+y)(Z+1)

=(z+1)(xy+1+x+y)

20 tháng 8 2017

dễ mà bn

mk bk lm mà lm biếng gõ qá

3 tháng 10 2016

\(a\left(b^2+c^2\right)+b\left(a^2+c^2\right)+c\left(b^2+a^2\right)+2abc\)

\(=ab^2+ac^2+a^2b+bc^2+cb^2+a^2c+2abc\)

\(=\left(a^2b+a^2c+ab^2+abc\right)+\left(abc+ac^2+b^2c+bc^2\right)\)

\(=a\left(ab+ac+b^2+bc\right)+c\left(ab+ac+b^2+bc\right)\)

\(=\left(a+c\right)\left(ab+ac+b^2+bc\right)\)

\(=\left(a+c\right)\left[\left(ab+ac\right)+\left(b^2+bc\right)\right]\)

\(=\left(a+c\right)\left[a\left(b+c\right)+b\left(b+c\right)\right]\)

\(=\left(a+c\right)\left(b+c\right)\left(a+b\right)\)